On-Site Runoff Management, Challenges and Prospects in Amalemba, an Urban Informal Settlement in Kakamega Municipality, Kakamega County, Kenya - Musonye, P. K.; Ucakuwun , E. K.; Munyao, T. M. (Africa Environmental Review Journal, 2022)
This study investigated the challenges and prospects of on-site runoff management in Amalemba informal urban settlement in Kakamega Municipality, Kenya. The study followed a qualitative research design. Visual observations, photography, individual and focus group interviews were used to collect data. The findings indicate that on-site and institutional practices complemented each other in management of runoff. This study therefore affirmed the importance of meaningful participation of residents in runoff management interventions and approaches that sustain ‘socio-human’ capacity for response in relation to impacts of runoff in informal urban settlements. In conclusion, the benefits of catchment-scale model for runoff management, the potential of green infrastructure and the necessity for policy transition to sustainable drainage systems in Amalemba informal urban settlement are of critical importance